DISCOVERY LEARNING ASSISTEND BY FRIENDLY MODEL ENVIRONMENTAL TEACHING AIDS THAT RELATED TO THE STUDENT’S SCIENTIFIC THINGKING ABILITIES - Izza Uliy Nuha; Faninda Novika Pertiwi (Pendidikan IPA, FMIPA, UNP, 2020)
This research is related to discovery learning assisted by environmentally friendly APS which is expected to be able to improved the scientific thinking ability of students of science class VIII at SMPN 1 Siman. The data generated from this study are the results of the experimental and control class post-test at the end of learning. The data analysis technique used t-test which has previously tested for pre requisites (homogeneity and normality). Based on the results of the study, it was found that t count = 10,407> t table = 2,069 so H1 was accepted. Furthermore, to find out the extents of the significance of the effect of discovery learning assisted by environmentally friendly APS related to the ability to think scientifically, one tailed follow-up test was conducted. Based on the results of one tailed further test shows that t0 (-10,407) <-t table (1,174), v (42.82), furthermore Ho is rejected H1 accepted. So there is a significant influence on the learning model of discovery learning assisted by environmentally friendly APS related to the scientific thinking ability of students of science class VIII at SMPN 1 Siman.